Comprehending Manipulative Tactics In Elections - Lubis, Muya Syaroh Iwanda; Purba, Budiman; Syahrah, Indi Regina; Adha, Ika; Lesminingrum, Lujeng (Universitas Dharmawangsa Medan, 2024)
General elections (Pemilu) are a strong foundation of democracy, but are often affected by various manipulative tactics used by political actors. This article aims to present a literature review of manipulative tactics that often appear in the context of general elections. We analyze various empirical and theoretical studies that highlight manipulative practices such as duping the masses, spreading fake news, money politics, voter intimidation, and gerrymandering. Through a synthesis of the literature, we identify the factors that drive the use of manipulative tactics and their impact on democratic integrity. Additionally, we explore efforts to address manipulative tactics, including stricter regulations, voter education, and the role of media and civil society in combating practices that undermine democratic processes. This analysis provides a deeper understanding of political dynamics in general elections and their relevance in the context of sustainable democratic development.